2014
DOI: 10.1590/s0080-623420140000300009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nursing diagnosis of fluid volume excess in patients undergoing hemodialysis

Abstract: Objective: To identify the prevalence of nursing diagnosis of fluid volume excess and their defining characteristics in hemodialysis patients and the association between them. Method: Cross-sectional study conducted in two steps. We interviewed 100 patients between the months of December 2012 and April 2013 in a teaching hospital and one hemodialysis clinic. The inference was performed by diagnostician nurses between July and September 2013. Results: The diagnostic studied was identified in 82% of patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 18 publications
1
19
0
7
Order By: Relevance
“…The ND of Excessive fluid volume were also present in all the older adults, confirming the literature -for example, according to Fernandes (2014), the accumulation of fluids is a frequent finding in hemodialysis patients (21) . Cavalcanti (2015) noted in his study that the ND of Excessive fluid volume had a higher incidence in older women who presented clinical conditions such as SAH and DM, a result also noticed in our analysis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The ND of Excessive fluid volume were also present in all the older adults, confirming the literature -for example, according to Fernandes (2014), the accumulation of fluids is a frequent finding in hemodialysis patients (21) . Cavalcanti (2015) noted in his study that the ND of Excessive fluid volume had a higher incidence in older women who presented clinical conditions such as SAH and DM, a result also noticed in our analysis.…”
Section: Discussionsupporting
confidence: 82%
“…This can be explained by the fact that blood pressure is directly related to the homeostasis of bodily fluid, which is maintained by the relationship between the volume of ingested and eliminated liquids, and this balance is regulated by the nervous system, hormone controls and by the kidneys. Thus, once the glomerular filtration rate is lower or null in patients with CKD, the elimination of fluids and electrolytes becomes inefficient, causing accumulation in the body and causing increased blood pressure in the interdialytic period (21)(22) . Being older adults the patients on hemodialysis with lower rate of survival and considering the frequent presence of the ND Excessive fluid volume, it is noted the need for early identification and effective management based on scientific knowledge of this diagnosis by the health team, since the body fluid overload in interdialytic period may cause edemas -among them, acute pulmonary edema, which is a common cause of hospitalization of older adult patients on hemodialysis (21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…(15) Among these patients, the mortality rate caused by infection after five years is 57%. (16) Risk for bleeding was described with a prevalence of 100%, (9) indicating that it should receive greater attention from professionals and researchers. (9,10) Risk for bleeding is directly related to platelet disorders, which prolong bleeding time.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Risk for shock was also considered relevant, in agreement with the findings of studies that identified this diagnosis with a prevalence of 100%. (9) Risk for falls has also been reported, (1,2) which can be caused by the hemodynamic oscillations that occur during hemodialysis. (13,14) Risk for allergy response was a highly valued diagnosis (RI=0.80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation